2019
DOI: 10.14202/vetworld.2019.271-276
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of non-specific immunity, gene expression, and disease resistance in Nile Tilapia, Oreochromis niloticus (Linnaeus, 1758), by the methanolic extract of the marine macroalga, Caulerpa scalpelliformis

Abstract: Aim: The objective of the present study was to test the immunostimulating potential of marine macroalga, Caulerpa scalpelliformis, in terms of non-specific immune responses, gene expression, and disease resistance of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758). Materials and Methods: O. niloticus was injected intraperitoneally with three different doses of methanol extract of C. scalpelliformis (CSME) (2 mg/kg, 20 mg/kg, or 200 mg/kg body weight), or MacroGardTM (commercial immunostimulant, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Food safety and food security due to food-borne infections are gaining interest in the past decade [1,2]. Anisakiasis, the zoonotic disease caused by nematode larvae of the genus Anisakis is considered as one of the most important biohazards in the fish products [3].…”
Section: Introductionmentioning
confidence: 99%
“…Food safety and food security due to food-borne infections are gaining interest in the past decade [1,2]. Anisakiasis, the zoonotic disease caused by nematode larvae of the genus Anisakis is considered as one of the most important biohazards in the fish products [3].…”
Section: Introductionmentioning
confidence: 99%
“…This difference is probably due to differences in serotype and biotype of bacteria, fish species, and temperature (Olga 2014). Besides that, the difference in test results and LD50 calculations is thought to be due to the very different sources of origin of bacteria and host fish used (Makrinos and Bowden 2016;Li et al 2017;Yengkhom et al 2019). Changes in the physical and chemical characteristics of the environment can increase the abundance and virulence of pathogenic organisms as can genetic mutation, factors which must have an important influence on the outcome of a situation in which pathogens challenge fish in the water (Tripathi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Vatsos and Rebours [ 43 ] reported that in aquaculture studies, the macroalgal compounds were either incorporated directly in the feeds (dry or live) or added directly into the water in which the fish and shrimp were grown. The efficacy of microalgae such as Chlorella vulgaris or Arthrospira platensis [ 44 , 45 ] and the polysaccharide fraction of the Caulerpa scalpelliformis or Padina gymnospora [ 46 , 47 ] was reported in Nile tilapia ( Oreochromis niloticus ) and common carp ( Cyprinus carpio ). In addition, microencapsulated macroalgal extracts were tested against Aeromonas salmonicida in Oreochromis mossambicus [ 48 ].…”
Section: Methods To Test the Antimicrobial Properties Of Novel Compoundsmentioning
confidence: 99%